White Coat Hypertension, relationship of stages of hypertension with end organ damage and diurnal variation of blood pressure in newly diagnosed hypertensive patients - Paudel, Navaraj; Karki, Prahlad; Shreshta, Nikesh Raj; Sharma, Sanjib Kumar (Journal of Advances in Internal Medicine, 2012)
Introduction - Systemic hypertension is a disease attributable for various cardiovascular events. White coat hypertension is under diagnosed in Nepal and is usually treated as hypertension. However its prevalence in Nepal is not known. The relationship of stages of hypertension and diurnal variation of blood pressure with end organ damage is a current topic of research however such studies haven’t been done in Nepal. Methods - A Cross-sectional, Descriptive study including 80 patients was conducted over a period of 1 year from February 2008 to March 2010 at B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan. Results - The prevalence of white coat hypertension was 9%. Considering stage one (JNC 7) patients only it was 17%. There was statistically significant association between rise in blood pressure and proteinuria (p=